Effect of hypnotherapy on paediatric cancer pain management in Indonesia: A quasi-experimental study - Hartini M.A, Sri; Nisa, Nafisatun; Pranata, Satriya; Oktiningrum, Mudy; Kristiawati, Sri Puguh (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Paediatric cancer patients often experience pain related to their condition and treatment. Hypnotherapy, a non-pharmacological intervention, has shown promise in pain management. This study aimed to investigate the effects of hospital-based hypnotherapy on pain reduction in paediatric cancer patients. Methods: A pretest-posttest experimental design without a control group was done with 60 paediatric cancer patients (ages 6–12) at Central General Hospital, Dr. Kariadi Semarang, Indonesia, from February to May 2024. Pain levels were assessed using the visual analogue scale (scores from 0 to 10) at the baseline, after two follow-up sessions at a week interval. Pain scores were recorded starting from 0 to 10. These were categorised as no score 0, mild (1–3), moderate (4–6) and severe (7–10) pain. Pain scores were compared using ANCOVA, but pain categories were compared using the chi-square test. Results: The mean age of the subjects was 8.8 (standard deviation, 4.2) years; 60% were boys. Hypnotherapy significantly reduced pain scores from a baseline mean score of 4.7 to 0.7 at the second assessment (P<0.001). Severe pain (13.3%) declined to 0%, and conversely, no pain category (0%) increased to 51.7% (P<0.001). Conclusion: Hypnotherapy at hospital significantly reduces pain in paediatric cancer patients. Therefore, hypnotherapy could be a valuable adjunct to conventional pain management strategies in paediatric oncology.